(untitled) (Research, Society and Development, 2020)
Agriculture and livestock have a strong participation in the Brazilian economy, and since the 70s improvements in the sector’s production pattern, through the intensification of the use of technologies in the production process, have led to a significant increase in productivity. Given the need to keep the farmer in the field, and given the degradation of pastures, the management of rural property, seeking to reconcile production with the conservation of natural resources is essential for the sustainability of the activity. The ISA tool - Sustainability Indicators in Agroecosystems - is an integrated system that verifies the socioeconomic and environmental performance of rural properties, is in the public domain, and was institutionalized in the state of Minas Gerais, in 2012. This work aimed to evaluate sustainability cattle, through a diagnosis of social, economic and environmental balance of two rural properties, located in the city of Malacacheta-MG, using the ISA tool. With the results obtained, it is intended to assist the rural producer, pointing out critical points to be corrected immediately and comparing the results by assessing which activity is more sustainable, dairy or beef cattle. The study presented for the livestock and beef cattle properties the sustainability indexes 0.50 and 0.53, respectively, where there is a range from 0 to 1, considering 0.7 the reference value for the proper functioning of the agroecosystem and to define it as sustainable. Based on the data collected, this paper aims to show how to maintain a sustainable property in an environmentally sound manner.